THE APPLICATION OF STRATEGIES COOPERATIVE LEARNING (CL) TO THE HISTORY OF ISLAMIC CULTURE IN THE FORMATION OF STUDENTS’ LEARNING CHARACTER AT MADRASAH TSANAWIYAH NEGERI SURAKARTA 1 - Diah Novita Fardani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This research examines the application of the cooperative learning (CL) model to learning the history of Islamic culture in shaping the character of the students at Madrasah Tsanawiyah Negeri Surakarta 1. This research uses qualitative and descriptive methods. The data collection technique used by the writer was through observation, interview, and documentation techniques as well as the object of research, namely the Cooperative Learning strategy in Islamic Cultural History Learning at Madrasah Tsanawiyah Negeri Surakarta 1 and the research subject was the Islamic cultural history teacher. The application of the cooperative learning (CL) strategy towards learning the history of Islamic culture in shaping the learning character of students at Madrasah Tsanawiyah Negeri Surakarta 1 refers to the type of index card match. In its application, this strategy is carried out properly in accordance with the steps, students become more active in following the learning process. This strategy also plays a very important role in shaping the character of student learning because in its application it is very relevant and responsive in accordance with the times.